TP53 Mutation Infers a Poor Prognosis and Is Correlated to Immunocytes Infiltration in Breast Cancer - Zhang, Ziwen; Hao, Ran; Guo, Qiusheng; Zhang, Sheyu; Wang, Xiaojia (Frontiers in Cell and Developmental Biology, 2021)
Abstract Background: This study aimed to investigate the TP53 mutation, its potential immune features, its prognostic value, and its impact on immune infiltration in patients with breast cancer (BC). Methods: We downloaded the somatic mutation data and clinicopathologic features of BC patients from the TCGA GDC database, UCSC Xena platform and International Cancer Genome Consortium (ICGC) database. The association between the TP53 mutation, clinicopathology features and overall survival (OS) in BC patients was analyzed. We evaluated the potential role of the TP53 mutation in the immune therapy response, including the tumor mutation burden (TMB), microsatellite instability (MSI) and tumor immune dysfunction and exclusion (TIDE). Moreover, ESTIMATE was employed to assess the ImmuneScore and StromalScore in BC patients. We also explored immunocyte infiltration related to the TP53 mutation and its potential mechanism. Immunohistochemistry (IHC) was performed to validate the association between the expression of CXCL1, CXCL10, and CCL20 and TP53 status. Results: We found that the TP53 mutation was significantly associated with the shorter OS (P = 0.038) and was also an independent predictive factor of OS for BC patients (P < 0.001). Compared to that in the wild type group, the TP53-mutant group showed a higher TMB value (P<0.001), MSI value (P = 0.077) and TIDE value (P < 0.001) with respect to BC patient immunotherapy. In addition, the ImmuneScore and StromalScore were both significantly increased in the TP53-mutant group (ImmuneScore: P < 0.001; StromalScore: P = 0.003). The results of CIBERSORT suggested that the TP53 mutation significantly promoted the infiltration of Tregs, T helper cells and M0-type macrophages. KEGG and GSEA enrichment results suggested that the IL-17 signaling pathway and antigen processing and presentation pathways were significantly enriched in the TP53-mutant group. Importantly, based on IHC results of immune-related hub-genes, the chemokines CXCL1, CXCL10 and CCL20 were significantly upregulated in the TP53-mutant group in BC patients. Conclusion: These results indicate that a TP53 mutation might serve as a biomarker for BC prognosis and is related to immunocyte infiltration in the tumor microenvironment.